The Politicization of Objects: Meaning and Materiality in The U.S. Cannabis Market - Huff, Aimee Dinnin; Humphreys, Ashlee; Wilner, Sarah J.S. (Journal of Consumer Research, 2021)
AbstractIn this article, we theorize how marketplace objects and their properties facilitate market legitimacy. Adopting assemblage theory, we examine a politically contested market—the U.S. recreational cannabis market—using retail sales data, public opinion polls and surveys, mainstream media coverage, and interviews with producers and consumers. We find that objects convey meaning in the market by creating sensory or discursive alignment between new or contested products and products from existing, legitimate markets, and by creating sensory or discursive distancing between new products and products in existing, illegitimate markets. We further find that different types of consumers play different roles in the overall legitimation process because they perceive alignments and misalignments differently. We present a conceptual model that links object meaning with the market and broader, cultural, and societal levels, demonstrating how materiality contributes to the overall legitimation of a politically contested market.